(untitled) - Shelly, Gary B.; Gary B. Shelly; Thomas J. Cashman; Misty E. Vermaat (Boston, Mass., 2007)
This new second edition includes sufficient material for a first course on Office 2003 applications. Challenge students with all new In the Lab exercises. Help students reinforce key skills with Case Studies and online tools on the Companion Web site. Our Microsoft Office 2003, Second Edition books continue with the innovation, quality, and reliability that you have come to expect from the Shelly Cashman Series
Keywords: Microsoft Excel; Microsoft Word; Microsoft Access; Microsoft PowerPoint; Microsoft Office